answer it fast.....its urgent ......only brainy can answer ......
Attachments:
![](https://hi-static.z-dn.net/files/d26/da52c9632699062a5d4d93d19aeaedd5.jpg)
nemo29:
yo
Answers
Answered by
2
Given that the sum of first 9 terms of an AP is 81.
We know that sum of n terms of an AP sn = (n/2)[2a + (n - 1) * d]
= > (9/2)[2a + (9 - 1) * d] = 81
= > (9/2)[2a + 8d] = 81
= > 9(2a + 8d) = 162
= > 2a + 8d = 18
= > a + 4d = 9 ------ (1)
Given that sum of its first 20 terms is 400.
= > (20/2)[2a + (20 - 1) * d] = 400
= > 10(2a + 19d) = 400
= > 2a + 19d = 40 ------------- (2)
On solving (1) * 2 & (2), we get
= > 2a + 8d = 18
= > 2a + 19d = 40
----------------------
-11d = -22
d = 2
Substitute d = 2 in (1), we get
= > a + 4d = 9
= > a + 4(2) = 9
= > a + 8 = 9
= > a = 1.
Therefore, The first term is 1 and the common difference d = 2.
Sum upto 15th term s15 = (n/2)[2a + (n - 1) * d]
= > (15/2)[2(1) + (15 - 1) * 2]
= > (15/2)[2 + 14 * 2]
= > (15/2)[30]
= > 15 * 15
= > 225.
Hope this helps!
We know that sum of n terms of an AP sn = (n/2)[2a + (n - 1) * d]
= > (9/2)[2a + (9 - 1) * d] = 81
= > (9/2)[2a + 8d] = 81
= > 9(2a + 8d) = 162
= > 2a + 8d = 18
= > a + 4d = 9 ------ (1)
Given that sum of its first 20 terms is 400.
= > (20/2)[2a + (20 - 1) * d] = 400
= > 10(2a + 19d) = 400
= > 2a + 19d = 40 ------------- (2)
On solving (1) * 2 & (2), we get
= > 2a + 8d = 18
= > 2a + 19d = 40
----------------------
-11d = -22
d = 2
Substitute d = 2 in (1), we get
= > a + 4d = 9
= > a + 4(2) = 9
= > a + 8 = 9
= > a = 1.
Therefore, The first term is 1 and the common difference d = 2.
Sum upto 15th term s15 = (n/2)[2a + (n - 1) * d]
= > (15/2)[2(1) + (15 - 1) * 2]
= > (15/2)[2 + 14 * 2]
= > (15/2)[30]
= > 15 * 15
= > 225.
Hope this helps!
Answered by
4
Put D = 2 in equation (3)
A = ( 9 - 4D )
A = ( 9 - 4 × 2 ) = 9-8 = 1
First term ( A ) = 1
And, Common Difference ( D ) = 2
Sn = N/2 × [ 2A + ( N - 1 ) × D ]
S15 = 15/2 × [ 2 × 1 + ( 15-1) × 2 ]
=> 15/2 × ( 2 + 28 )
=> 15 /2 × 30
=> ( 15 × 15 ) = 225
Hence,
Sum of first 15th term = 225.
★ HOPE IT WILL HELP YOU ★
A = ( 9 - 4D )
A = ( 9 - 4 × 2 ) = 9-8 = 1
First term ( A ) = 1
And, Common Difference ( D ) = 2
Sn = N/2 × [ 2A + ( N - 1 ) × D ]
S15 = 15/2 × [ 2 × 1 + ( 15-1) × 2 ]
=> 15/2 × ( 2 + 28 )
=> 15 /2 × 30
=> ( 15 × 15 ) = 225
Hence,
Sum of first 15th term = 225.
★ HOPE IT WILL HELP YOU ★
Attachments:
![](https://hi-static.z-dn.net/files/d51/0ae5c895fb19513253c5787e8538143e.jpg)
![](https://hi-static.z-dn.net/files/d06/bec069d5ba1c7613907f065094713b54.jpg)
Similar questions